Factors influencing (Reputation, Perceived Value, Location, Convenience, Internal Environment, and Staff) on Customer Loyalty through Satisfaction: Perspective from Malaysia Hypermarket Industry - Kadhim, Kadhim Ghaffar; Harun, Amran; Hamawandy, Nawzad Majeed; Rahman, Shorsh Khaild; Jamil, Diyar bdulmajeed; AL .Bewani, Hemn Adl Wali (The journal of contemporary issues in business and government, 2021)
The purpose of this paper is to contribute to knowledge on the influence to the role of hypermarket services in crafting reputation, perceived value, location, convenience, internal environment, and staff to customers, thus creating satisfied and loyal customers (hypermarkets).With the support of empirical evidence and rational arguments, a set of eight (8) hypotheses were proposed for testing. A sample of 384 respondents visiting hypermarket in Kuala Lumpur using a convenience sampling method was used. Statistical analysis was done through SPSS for primary analysis and Smart PLS for analysis of the outer model and testing the relationships hypothesized. Findings revealed that all the hypotheses were significantly supported. The originality and value of this paper is the study of consumer-oriented hypermarket services as a variable that allows competitive differentiation of the company, by improving the relationship with the consumers and the generation of satisfaction and loyalty. One of the major conclusions of the study is that hypermarket services can yield optimal performance for customer satisfaction and customer loyalty if it is combined with the knowledge, experiences, and outstanding abilities in the use of hypermarket services in crafting reputation, perceived value,location, convenience, internal environment, and staff to customers, thus creating satisfied and loyal customers.